Optimization for Next Generation Wireless System Using Radio Over Fiber in Terms of Topology - Othman, Shwan Asaad Othman; Türkoğlu, İbrahim (Fırat University, 2017)
This dynamic execution of Radio over Fiber (RoF) joins utilizing minimal effort optoelectronic parts are evaluated for dispersed receiving wire applications in cutting edge remote frameworks. Vital configuration issues are examined and an illustrated the outline is exhibited for a remote framework requiring the transmission of four radio channels for every connection course.  Each of these channels has 100 MHz transmission capacity, balance many-sided quality of 256-QAM and 2048 OFDM subcarriers. The Radio Access Network (RAN) is using for all types of mobile system, each of this RAN have a different topology such as star, circle, tree, etc. On the other hand, to creating and using a new RAN is better to use mesh topology which is suitable for the new system. In the same way, in the field of using new RAN, topology can be apply as a mesh, which includes RoF. It also call as next generation mobile system for the new system, instead of using microwave it can use fiber optic that is why microwave are ignored. This type of use is more useful in terms of quality and system optimization for 4G and similar systems.